2018
DOI: 10.1155/2018/5758191
|View full text |Cite
|
Sign up to set email alerts
|

Tribulus terrestris Protects against Male Reproductive Damage Induced by Cyclophosphamide in Mice

Abstract: Tribulus terrestris (TT) has been considered as a potential stimulator of testosterone production, which has been related with steroidal saponins prevailing in this plant. Cyclophosphamide (CP) is the most commonly used anticancer and immunosuppressant drug, which causes several toxic effects, especially on the reproductive system. Patients who need to use CP therapy exhibit reduced fertility or infertility, which impacts both physically and emotionally on the decision to use this drug, especially among young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 37 publications
2
42
0
1
Order By: Relevance
“…Furthermore, cytotoxic cancer therapies such as cyclophosphamide have detrimental effects upon spermatogenesis [ 136 ]. Several natural products in this review were demonstrated as applicable reproductive agents, reducing the notorious effects of EDCs as well as chemotherapy such as mitomycin C, cyclophosphamide, cisplatin, and adriamycin [ 9 , 10 , 14 , 25 , 43 , 46 , 50 , 90 ]. Accordingly, the use of natural materials will be an effective alternative to prevent and treat infertility caused by oxidative stress due to increased exposure to chemicals.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, cytotoxic cancer therapies such as cyclophosphamide have detrimental effects upon spermatogenesis [ 136 ]. Several natural products in this review were demonstrated as applicable reproductive agents, reducing the notorious effects of EDCs as well as chemotherapy such as mitomycin C, cyclophosphamide, cisplatin, and adriamycin [ 9 , 10 , 14 , 25 , 43 , 46 , 50 , 90 ]. Accordingly, the use of natural materials will be an effective alternative to prevent and treat infertility caused by oxidative stress due to increased exposure to chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 75 studies focused on plant derived compounds, five studies on animal derived compounds, and only one study presented a natural substance of fungal origin. Natural products which were mentioned more than once include Curcumin, Echinacoside, and extracts from Cistanche tubulosa , Date palm pollen, Diallyl sulfide , Lycium barbarum , Linn., Lepidium meyenii Walp., Morinda oleifera Lam, and Tribulus terrestis Linn [ 6 , 9 , 22 , 50 , 51 , 54 , 55 , 63 , 64 , 65 , 104 , 105 ]. Especially, the effects of Tribulus terrestis Linn.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations